Study Of The Structural Properties Of Al-Zn Compounds Manufactured By Powder Technology And Copper-Reinforced - Sukaina Iskandar Yusuf; Sabri Jasim Mohammad; , Mohsin Hasan Ali (Tikrit Journal of Pure Science, 2024)
Due to the importance of aluminium compounds in many industrial fields, therefore, in this study, copper-reinforced (Al-Zn) compounds were prepared in different proportions (0%, 0.4%, 1.2%, and 2%), using the powder technique. The structural properties of the compounds under study were investigated using XRD and EDS tests at room temperature. It was found through the XRD results that the samples were polycrystalline (cubic, tetragonal, monoclinic, and hexagonal). The results of the crystallinity analysis showed that sample (Al-Zn-(0%)Cu) was (12.73%) crystallized, sample (Al-Zn-(0.4%)Cu) was (32.125%) crystallized, sample (Al-Zn-(1.2%)Cu) was (42.771%) crystallized, and sample (Al-Zn-(2%)Cu) was (50.179%) crystallized. Theoretical density of the phases was determined for each sample using independent calculations, taking into consideration some factors such as variations in atomic mass, the number of atoms of the constituent elements, and the size of the unit cell.